Regra e criatividade no comportamentalismo radical de B.F. Skinner - Ferreira, Paulo Roberto dos Santos (Universidade Federal de São Carlos, 2010)
Through a critical reading of Skinner s works it was intended to clarify ambiguitiesconcerning scientific and philosophical communities regarding the concepts of rule and verbalstimulus. It was also sought an appropriate statement of creative behavior and thoughtconcepts according to Skinner s Radical Behaviorism. This research had, therefore, a twofoldobjective which was to identify: (1) Skinnerian interpretation of creative behavior and thoughtand (2) Skinner s conception of rule and rule-governed behavior. The steady relation pointedout by B. F. Skinner among the concepts of verbal stimulus, rule and creative behavior and, atthe same time, the controversy spread out by Skinner s commentators and scientists, seeking asufficient and non-ambiguous definition of rule, mainly justifies this study enterprise. Usually, these commentators treat verbal stimulus and rule concepts as identical, being thisidentity a satisfying condition for a definition of the latter as a corollary of the statementsrelating to the Verbal Behavior matter. Moreover, commonly Skinner s work reviewersdefine creative behavior as a variation or unit recombination, which implies supposing thatcreative behavior does not differ from other emissions of operant behavior, since the variationis a ubiquitous characteristic on behavior emissions according to Skinnerian model ofselection by consequences. Part of this study consisted in demonstrating how an explanationof the distinctions existing between verbal stimulus and rule can collaborate with a preciseand productive definition of complex and creative human behavior without losing sight of thebehavioral interpretation object s inherent characteristics. Aiming these goals, the course ofresearch went the following route: (1) identification, in texts by the author, of the conceptsunderlying behavioral interpretation; (2) a systematic analysis of the verbal stimulus concepton its possible behavioral functions and, thus, also its relation to the rule concept; (3) theformulation of an alternate interpretation of creative behavior and rule-governed behaviorbased on Skinnerian explanatory system. Finally, there was a brief foray into formulations ofDewey and Wertheimer on creative behavior and thinking in order to, thereby, outlinepossible convergence on interpretative perspectives brought by the three authors. Among themost important results, it was demonstrated that: (1) simply presume variability does notexplain creative behavior, not only from B. F. Skinner perspective, but neither from JohnDewey s and Max Wertheimer s; (2) four Skinner notions are fundamental in a conceptualrelation between behavioral analysis and interpretation: strength, property, continuum andcomplexity; (3) rule is not defined as verbal stimulus and neither it is a conceptual subcategoryof this kind of stimulation; (4) creative behavior is necessarily complex andorganized, and its structure is functionally defined; (5) rule is one of the creative complexbehavior elements; and (6) rule is a new complex discriminative stimulus with a functionalcomplication typical of a creative emission, although it is not restricted to this behavioralcontext.
Keywords: Psicologia - filosofia; Criatividade; Skinner, B. F. (Burrhus Frederick), 1904-1990; Comportamento humano; Regras; Comportamento verbal; Comportamento governado por regra; Comportamentalismo radical; Creativity; B. F. Skinner; Rule-governed behavior; Verbal behavior; Radical behaviorism; CIENCIAS HUMANAS::FILOSOFIA